2014
DOI: 10.1160/th13-06-0509
|View full text |Cite
|
Sign up to set email alerts
|

Anti-prothrombin (aPT) and anti-phosphatidylserine/prothrombin (aPS/PT) antibodies and the risk of thrombosis in the antiphospholipid syndrome

Abstract: Antibodies to prothrombin are detected by directly coating prothrombin on irradiated ELISA plates (aPT) or by using the phosphatidylserine/prothrombin complex as antigen (aPS/PT). Although these antibodies have both been associated with antiphospholipid syndrome (APS) and a correlation between the two assays have been reported, it seems that aPT and aPS/PT belong to different populations of autoantibodies. It was our objective to systematically review the available evidence on aPT and aPS/PT antibodies and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
182
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 65 publications
7
182
2
5
Order By: Relevance
“…There has been a flurry of activity in the development of ELISAs that detect aAbs targeting the PS/PT complex, with some promising results with regard to their potential diagnostic value. 50 Larger studies involving multiple centers and, preferably, multinational research collaborations will be necessary before accepting the clinical utility of such findings. Several other active areas of ongoing research based on promising emerging data include determining the diagnostic utility of a novel domain I-specific anti-␤ 2 GPI ELISA and the relevance of IgA anti-␤ 2 GPI aAbs.…”
Section: Nonclassification Criteria Laboratory Assaysmentioning
confidence: 99%
“…There has been a flurry of activity in the development of ELISAs that detect aAbs targeting the PS/PT complex, with some promising results with regard to their potential diagnostic value. 50 Larger studies involving multiple centers and, preferably, multinational research collaborations will be necessary before accepting the clinical utility of such findings. Several other active areas of ongoing research based on promising emerging data include determining the diagnostic utility of a novel domain I-specific anti-␤ 2 GPI ELISA and the relevance of IgA anti-␤ 2 GPI aAbs.…”
Section: Nonclassification Criteria Laboratory Assaysmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] A recent systematic review suggested that both antibodies against prothrombin, aPT-A and aPS/PT, are risk factors for thrombosis, but that aPS/PT represent a stronger risk factor for arterial and/or venous thrombosis when compared to aPT-A. 21 In two prospective studies, the presence of aPT-A has been reported as a predictor of thromboembolic events in patients with aPL, mainly in those patients positive for LA. 22,23 Many reports have shown the clinical utility of aPS/PT in the diagnosis of APS.…”
Section: Introductionmentioning
confidence: 99%
“…When evaluating the diagnostic accuracy of several aPL specificities combinations, the profile including LA + anti-β2GPI + aPS/PT held the best diagnostic accuracy for APS even when subdividing the study group into those with thrombosis and those with pregnancy loss [29]. In addition, aPS/PT have been confirmed as a strong risk factors for thrombosis, irrespective of the site and type of thrombosis.…”
Section: Prothrombin/phosphatidylserine Complexmentioning
confidence: 94%
“…In addition, aPS/PT have been confirmed as a strong risk factors for thrombosis, irrespective of the site and type of thrombosis. Their presence incurred in an odds ratio (OR) for thrombosis 3 to 18 times higher than in various control groups [29].…”
Section: Prothrombin/phosphatidylserine Complexmentioning
confidence: 99%
See 1 more Smart Citation